Reaction pathways and redox states in α-selective cobalt-catalyzed hydroborations of alkynes - Blasius, Clemens K.; Vasilenko, Vladislav; Matveeva, Regina; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie, 2020)
Cobalt(II) alkyl complexes supported by a monoanionic NNN pincer ligand are pre-catalysts for the regioselective hydroboration of terminal alkynes, yielding the Markovnikov products with α:β-(E) ratios of up to 97:3. A cobalt(II) hydride and a cobalt(II) vinyl complex appear to determine the main reaction pathway. In a background reaction the highly reactive hydrido species specifically converts to a coordinatively unsaturated cobalt(I) complex which was found to re-enter the main catalytic cycle.
Version of record online: 15 October 2020
Gesehen am 25.10.2021